Chaotic Behavior in a Flexible Assembly Line of a Manufacturing System - Sajid, M.; Almufadi, F. A.; Jahanzaib, M. (Engineering, Technology & Applied Science Research, 2015)
The purpose of the present work is to study the chaotic behavior in a flexible assembly line of a manufacturing system. A flexible assembly line can accommodate a variety of product types. Result analysis is performed to obtain time persistent data. The behavior of the system is observed for Work-In-Process, as assembling systems are sensitive during processing. It is found that the average Lyapunov exponent is positive in the considered case, and thus chaotic behavior may be present in flexible assembly lines.